Making Nonconjugated Small-Molecule Organic Radicals Conduct - Yu, Ilhwan; Jo, Yerin; Ko, Jaehyoung; Kim, Dae-Yoon; Sohn, Daewon; Joo, Yongho (AMER CHEMICAL SOC, 2020)
Charge neutral, nonconjugated organic radicals have emerged as extremely useful active materials for solid-state electronic applications. This previous achievement confirmed the potential of radical-based macromolecules in organic electronic devices; however, charge transport in radical molecules has not been studied in great detail from a fundamental perspective. Here we demonstrate the charge transport in a nonconjugated organic small radical, 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (h-TEMPO). The chemical component of this radical molecule allows us to form a single crystal via physical vapor deposition (PVD). While the charge transport of this macroscopic open-shell single crystal is rather low, thermal annealing of the well-defined single crystal enables the molecule to have a rapid charge transfer reaction due to the electronic communication of open-shell sites with each other, which results in electrical conductivities greater than 0.05 S m(-1). This effort demonstrates a drastically different model than the commonly accepted conjugated polymers or molecules for the creation of next-generation conductors.
Keywords: PHYSICAL VAPOR GROWTH; FIELD-EFFECT-TRANSISTOR; CHARGE-TRANSPORT; THIN-FILM; SEMICONDUCTORS; POLYMER; ORGANIZATION; PERFORMANCE; NONVOLATILE; CRYSTALS